Crystal structure of (E)-2-((3-fluoropyridin-4-yl)methylene)-7-methoxy-3,4-dihydronaphthalen-1(2H)-one, C17H14FNO2 - Wang Chen; Wang Lei; Meng Qing-Guo; Huang Zhi-Xin; Ma Nuan-Nuan; Wang Chun-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C17H14FNO2, monoclinic, P21/n (no. 14), a = 8.0937(8) Å, b = 7.1326(6) Å, c = 22.367(2) Å, β = 90.863(9)°, V = 1291.1(2) Å3, Z = 4, Rgt(F) = 0.0404, wRref(F2) = 0.0974, T = 99.97(16) K.